Qualidade de vida e Satisfação com o trabalho de profissionais de Educação Física atuantes em academias da cidade de Pelotas-RS - Bevilacqua, Lidiane Amanda (2013)
Acting as centers focused on physical exercise , the academies have undergone a series of transformations over time , intensified since the 1970s , when the cult of form gained representative dimensions in society . With the growing number of academies increased interest in checking the working conditions and issues related to health and quality of life for professionals working in these services . The quality of life of the professionals can be influenced by the level of perceived satisfaction in their work environment . Job satisfaction aims to provide answers to an emotional state and experiences encountered in the workplace . This response can be presented as a way of being and feeling positive towards the profession , or conversely , when such feeling and way of being in the profession do not occur , characterized by the presence of dissatisfaction . Objective: This study aims to investigate the job satisfaction and quality of life for professionals working in the gyms of Pelotas - RS , and examine their relationships and associated factors . Methodology : This was a descriptive , observational , cross-sectional . Data collection will be conducted through a questionnaire containing questions relating to the part , sociodemographic , behavioral and nutrition , quality of life and job satisfaction of professionals working in the academies of Pelotas